Appartenenze ed esclusioni - Frederica Paletti (Rechtsgeschichte - Legal History)
From the second half of the 16th century onwards, Venice ordered the cities of its mainland dominions (Terraferma) to adopt substantial legislation and to create special magistrates aimed at countering the dangers posed by »disruptors of the quiet and peaceful life«: foreigners, beggars, pauperes, vagrants and bandits. The provisions of the decrees Venice sent to the Terraferma inevitably intertwined with the ius proprium already in force in the individual civitates. The subjects receiving this copious regulatory production did not correspond to a single legal type, nor did they enjoy the same legal status, since the terms employed by the Venetian and mainland legislation to indicate them were polysemic, the result and expression of different regional historical-social moments and dynamics. In the decades crucial to the formation of modern states, the intensifying iurisdictio exercised by Venice translated in its mainland territories into an increasing concern with what we might call the »other side of citizenship«. A growing number of obligations, prohibitions, exclusionary measures and, much more rarely, privileges were set up by the communities to deal with non-residents and other marginal groups and individuals. The investigation of the contents of these measures provides a vivid insight into the different forms that the concept of »citizenship«, understood as a link that binds the individual to the political community, received in those decades. Its complex, multiple layers of meaning can only be grasped when the institutional and legal relations between Venice and the cities of the Terraferma are taken into account.